Improved visible-light photocatalytic activity of TiO 2 co-doped with copper and iodine - Dorraj, Masoumeh; Goh, Boon Tong; Sairi, Nor Asrina; Woi, Pei Meng; Basirun, Wan Jefrey (Elsevier, 2018)
Cu-I-co-doped TiO 2 photocatalysts active to visible light absorption were prepared by hydrothermal method and calcined at various temperatures (350 °C, 450 °C, and 550 °C). The co-doped powders at 350 °C displayed the highest experimental Brunauer–Emmett–Teller surface area and lowest photoluminescence intensity, which demonstrated that a decrease in electron–hole recombination process. The synthesis of co-doped TiO 2 was performed at this optimized temperature. In the co-doped sample, the Cu 2+ doped TiO 2 lattice created a major “red-shift” in the absorption edge due to the presence of the 3d Cu states, whereas the amount of red-shift from the I 5+ doping in the TiO 2 lattice was minor. Interestingly, the presence of Cu 2+ species also boosted the reduction of I 5+ ions to the lower multi-valance state I − in the TiO 2 lattice by trapping the photogenerated electrons, which resulted in effective separation of the photogenerated charges. The Cu-I-co-doped TiO 2 was able to degrade methyl orange dye under visible-light irradiation with improved photocatalytic activity compared with the single metal-doped TiO 2 and pure TiO 2 because of the strong visible light absorption and effective separation of photogenerated charges caused by the synergistic effects of Cu and I co-dopants.